2005
DOI: 10.1542/peds.2004-2505
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Failure and Hypercoagulability in a Toddler With Lemierre's Syndrome

Abstract: ABSTRACT. A 3.5-year-old healthy boy with 4 days of fever was referred to the emergency department for respiratory distress. The physical examination was remarkable for stupor, tachycardia, tachypnea, and dyspnea. Initial blood tests showed pancytopenia. He rapidly developed torticollis. I n 1936, Lemierre described a syndrome that consisted of septicemia with an anaerobic agent (later defined as Fusobacterium necrophorum), thrombophlebitis of cervical veins, and distal metastatic abscesses, developed several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 8 publications
0
21
0
6
Order By: Relevance
“…One child was heterozygous for factor V Leiden. Schmid et al (331) presented a clinical case of Lemierre's syndrome with confirmed internal jugular vein thrombosis and pulmonary lesions. Screening for hypercoagulability revealed two known risk factors: a mutation in the prothrombin gene and elevated lipoprotein a.…”
Section: Host Factorsmentioning
confidence: 99%
“…One child was heterozygous for factor V Leiden. Schmid et al (331) presented a clinical case of Lemierre's syndrome with confirmed internal jugular vein thrombosis and pulmonary lesions. Screening for hypercoagulability revealed two known risk factors: a mutation in the prothrombin gene and elevated lipoprotein a.…”
Section: Host Factorsmentioning
confidence: 99%
“…A molecular thrombophilic predisposition was observed in children with invasive infection [12][13][14][15], and a single nucleotide polymorphism in the toll-like receptor 5 gene was found in an affected child [12].…”
Section: Pathogenesismentioning
confidence: 99%
“…The prevalence of thrombophilia in LS is unknown. Some case reports have described its coexistence with LS as a possible contributing factor to thrombosis presentation or evolution in this disorder [20,41]. Not all patients in our cohort were comprehensively evaluated for congenital or acquired thrombophilia, and thus we could not evaluate its role in thrombosis outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…The majority of the publications we cite here reported on exclusively adult patients with LS (age at diagnosis ≥18 years) [5,10,11,13,14,15,16,21,28,32,33,34,37,38,39]. Comparatively, data published in the pediatric population is very limited; however, we attempted to include all case reports and studies of exclusively pediatric patients as well [4,6,8,9,19,23,25,40,41,42]. Similar to our study, a few case reports included a combination of pediatric and adult cases [5,17,18,25,35].…”
Section: Discussionmentioning
confidence: 99%